CALCULATION OF HYDRO-STREAM PARAMETERS DURING FLUID ACCELERATION IN HALF-CLOSED CHAMBER WITH EXIT TO FLAT SURFACE - V. V. Ivashechkin; D. A. Kozlov; E. I. Mikhnevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a method for calculation of maximum fluid velocity in a process chamber that is installed with a gap relative to the surface to be cleaned while burning gaseous mixture composed of 2H2 + O2 in the chamber. On the basis of the analytical solution for the movement of unsteady-state flow of viscous incompressible fluid taking into account a number of assumptions an expression for calculating maximum stream velocity at the end of acceleration period is obtained. Action force of the fluid on the surface is calculated from a momentum equation.  An example for calculation of hydro-stream parameters is given in the paper.